(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this experimental investigation the effect Experimental study on the effect of surface modification Nanofluid on thermal efficiency of solar collector with vibrator helical tube. The collector consists of a cylindrical glass tube with surface modified helical coil as the receiver of the solar energy. Also the efficiency with MWCNT nanofluid far from isoelectric points higher than other nanofluid. The MWCNT/water nanofluids at 0.1%, 0.3%, and 0.5% molecule volume fixations were set up with the expansion of surfactant by utilizing the two-venture strategy. It is examined that the readied MWCNT/water nanofluids show great solidness even following 45 days of planning and there is no impressive store of nanotubes on the cylinder inward divider. It is likewise contemplated that there is no impending danger of taking care of MWCNT and considered that there is no critical disintegration of wound cylinder internal divider surface even after a few trials. Thusly, the MWCNT/water nanofluids are the other warmth move liquids for conventional liquids in the helically looped tube heat exchanger to improve the warmth move with extensive pressing factor drop. Satisfactory execution of materials at raised temperatures is a possible issue in numerous frameworks inside the synthetic, petrol, cycle, and force producing enterprises. Debasement of materials happens due to connection between the primary material and the openness climate.